Experiences in receiving financial incentives to access HIV care in Johannesburg, South Africa - Sara Rachel Schlehr; Leanne Singh; Athini Nyatela; Sizwe Nqakala; Samanta T. Lalla-Edward (AOSIS, 2022)
Background: Financial incentivisation has been used to improve all steps of the HIV cascade with varying results. Most studies conducted on the matter are of a quantitative nature, not giving enough space for in-depth understanding as to why financial incentives work or do not work. Objectives: To describe experiences with, and opinions on, the use of financial incentives to promote linkage to and retention in care from the perspective of people living with HIV. Method: We performed a qualitative cross-sectional study. In-depth interviews were conducted with adult men and women with HIV accessing health services or research study visits. After codebook development, NVivo 12 software was used to code and analyse the data. Results: Through the provision of financial incentives, participants were able to cover basic needs. However, some deemed financial incentives as a form of income rather than a nudge to spark interest in changing their health behaviour. Participants communicated that a need for some type of incentive exists and recommended food vouchers as the best possible solution. Conclusion: Financial incentivisation can facilitate engagement in the HIV care continuum through providing support to people living with HIV. What this study adds: This study complements the body of research that explores the feasibility of using incentives and which of them may be most beneficial in encouraging patients with HIV to enter into and sustain HIV care.